2023
DOI: 10.1002/ana.26736
|View full text |Cite
|
Sign up to set email alerts
|

Activated Wake Systems in Narcolepsy Type 1

Ling Shan,
Suzan Linssen,
Zoe Harteman
et al.

Abstract: ObjectiveNarcolepsy type 1 (NT1) is assumed to be caused solely by a lack of hypocretin (orexin) neurotransmission. Recently, however, we found an 88% reduction in corticotropin‐releasing hormone (CRH)‐positive neurons in the paraventricular nucleus (PVN). We assessed the remaining CRH neurons in NT1 to determine whether they co‐express vasopressin (AVP) to reflect upregulation. We also systematically assessed other wake‐systems, since current NT1 treatments target histamine, dopamine, and norepinephrine pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…Recent studies had found a reduced number of neurons expressing and hyperactivity of the remaining CRH neurons in the paraventricular nucleus (PVN) of the hypothalamus in patients with NT1. 53 , 54 CRH increased the rate-limiting enzymes of biosynthesis for NE and 5-HT, which in turn inhibited the activation of NE and 5-HT. 55 Antagonists of CRH1 receptors showed antidepressant-like effects, confirming the relationship between CRH and anxiety and depression.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies had found a reduced number of neurons expressing and hyperactivity of the remaining CRH neurons in the paraventricular nucleus (PVN) of the hypothalamus in patients with NT1. 53 , 54 CRH increased the rate-limiting enzymes of biosynthesis for NE and 5-HT, which in turn inhibited the activation of NE and 5-HT. 55 Antagonists of CRH1 receptors showed antidepressant-like effects, confirming the relationship between CRH and anxiety and depression.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the relationship between anxiety and depressive symptoms in NT1 is yet to be fully understood. In a post-mortem study, there was a surprisingly substantial reduction in the number of CRH-positive neurons in the paraventricular nucleus in NT1 [27]. The CRH signal was preserved in other brain areas.…”
Section: Anxietymentioning
confidence: 96%
“…Of note, there is a difference between acute stress response and chronic stress levels. In a follow-up study, almost all of the 12% 'surviving' paraventricular CRH neurons expressed vasopressin [27]. This peptide also plays an essential role in the HPA axis and strongly potentiates the action of CRH on cortisol release.…”
Section: Stress Responsementioning
confidence: 96%
“…In idiopathic RBD, REM sleep without atonia arises from the dysfunctioning of REM-regulating pontomedullary nuclei, primarily through glutamatergic neurons in the subcoeruleus [ 16 ]. Changes in neuron counts outside the hypothalamus have so far not been identified in narcolepsy type 1 [ 17 , 18 ], and loss of hypocretinergic innervation of brainstem REM circuits and the basal ganglia seems a more reasonable hypothesis for RBD symptoms in narcolepsy type 1. Different underlying pathophysiology could account for the nuanced distinctions in RBD phenotypes, such as the typically younger onset in narcolepsy compared to idiopathic RBD [ 15 ].…”
mentioning
confidence: 99%